Influence of interleukin-1 on neutrophil function and resistance to streptococcus suis in young pigs - Shi, Jishu N.; Chengappa, M. M.; McVey, D.S.; Blecha, Frank; Goodband, Robert D.; Nelssen, Jim L.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nonspecific immunity is usually lower in young pigs than adults. Consequently, enhancing the young pig's nonspecific immune capability may be beneficial for the health and performance of early-weaned pigs. Twenty, 9-d-old, crossbred pigs were allotted by litter and weight into two treatment groups: recombinant bovine interleukin- 1β (rBoIL-1β; 5 μg/kg, intramuscularly at 9 and 10 d of age)) or control. Pigs were weaned at 10 d of age and housed in an isolation facility with ad libitum access to water and a pelleted diet formulated to meet the nutrient requirements and provide maximum growth of early-weaned pigs. Blood samples were obtained on 9, 12, 15, and 18 d of age for determination of several neutrophil function assays including: bactericidal activity, antibody-dependent cellular cytotoxicity (ADCC), and superoxide anion production. Pigs were challenged with S. suis (serotype 2) at 18 d of age. Neutrophil-mediated ADCC was increased at 12, 15, and 18 d of age in pigs treated with rBoIL-1β. Two days postweaning, neutrophil-mediated lysis of Staphylococcus aureus was lower in control pigs when compared to rBoIL-1β-treated pigs (6.6 vs 13.3%). Superoxide anion production was not influenced by rBoIL-1β treatment. Clinical signs of S. suis infection were less severe in pigs administered rBoIL-1β. These data suggest that rBoIL-1β increases neutrophil function and resistance to S. suis in early-weaned pigs.
Keywords: Swine; Early weaning; Immunity; Immune enhancement